Type 2B von Willebrand Disease: Early Manifestation as Neonatal Thrombocytopenia - Kranzhöfer, David; Pavlova, Anna; Schneider, Hendryk; Franck, Peter; Glonnegger, Hannah; Büchsel, Martin; Yoshimi-Nöllke, Ayami; Oldenburg, Johannes; Zieger, Barbara (Hämostaseologie, 2021)
Here, we report about a preterm female newborn with a prolonged course of severe thrombocytopenia and hematomas. The family history was positive for von Willebrand disease type 2B (VWD 2B). Diagnosis of VWD 2B was identified analyzing von Willebrand factor (VWF) parameters (VWF:antigen, VWF:activity, VWF multimer analyses) and performing light transmission aggregometry (with half concentration of ristocetin). In addition, the diagnosis was confirmed by molecular genetic analysis: identification of a disease-causing missense mutation (Val1316Met) in the VWF gene associated with a severe course of VWD 2B, which had been previously reported. Treatment with a VWF-containing plasma concentrate was initiated. Because the combination of prematurity and very low platelet count is often associated with intracranial bleeding, at the beginning platelet concentrates were transfused. Fortunately, the patient did not develop serious bleeding episodes. Interestingly, the patient had a mutation in the VWF gene, which had been described to be associated with aggravation of thrombocytopenia especially in stressful situations. Therefore, we replaced venous blood withdrawals by capillary blood samplings when possible and, consequently, we observed an increase of the platelet count after this change in management. At the age of 2 months, the patient was discharged after stabilization of the platelet count without any bleeding signs and without a need of long-term medication.
Keywords: von Willebrand disease; thrombocytopenia; neonate